2022
DOI: 10.2147/idr.s346705
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Pathogenicity Islands and Giardia lamblia Cysteine Proteases in Role of Coinfection and Pathogenesis

Abstract: Helicobacter pylori is a well-known human-specific stomach pathogen that infects more than half of the world's population. The infection with this bacterium can cause a variety of gastrointestinal problems, including chronic gastritis, peptic ulcers, and even cancer. H. pylori is a highly infectious bacterium. H. pylori causes an increase in gastric mucosa pH or gastric mucosa intestinal metaplasia. These modifications in the stomach environment are necessary for G. lamblia colonization to occur. Giardia lambl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…An increase in the per cent of male infection may be due to males' behaviour in dealing with their surrounding environment. The category most movement, contact with external environmental factors in terms of their survival for a long time outside their homes to practice the business, which imperative them to eat and drink in crowded restaurants and shops that not clear and street vendors and play games more than female in addition to bad habits such as put fingers in the mouth and biting nails all these lead to increasing infect with the parasite especially in male so that the male is more susceptible than female (16,17,18,19,20,15,21,22,23). While Heideri and Rokni (24) and Al-fatli (25) refer to the absence of a significant difference in the incidence of the infection between males and females and other studies, found that the per cent of disease in females is more than males (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the per cent of male infection may be due to males' behaviour in dealing with their surrounding environment. The category most movement, contact with external environmental factors in terms of their survival for a long time outside their homes to practice the business, which imperative them to eat and drink in crowded restaurants and shops that not clear and street vendors and play games more than female in addition to bad habits such as put fingers in the mouth and biting nails all these lead to increasing infect with the parasite especially in male so that the male is more susceptible than female (16,17,18,19,20,15,21,22,23). While Heideri and Rokni (24) and Al-fatli (25) refer to the absence of a significant difference in the incidence of the infection between males and females and other studies, found that the per cent of disease in females is more than males (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…For H. pylori to colonize the gastric mucosa, the bacteria migrates from epithelial to the basal layer driven by chemotaxis with a pH closer to 7.0. There are 4–7 polar sheathed flagella that achieve this process [ 21 ]. Once the migration occurs, in the next stage adhesin-receptor interaction takes place.…”
Section: Hpylori's Pathogenicity and Carcinogenicitymentioning
confidence: 99%
“…During this process, metabolism begins to slow down as the cells close and enter a resting state. Eventually, the cysts are eliminated with the host's feces [11].…”
Section: Giardia Intestinalismentioning
confidence: 99%